Necrotizing Pneumonia In Infant: Rare Complication of Community Acquired Pneumonia - Adhikari, Suman Bikram; Chaudhary, Ramananda Prasad (Journal of Nepal Paediatric Society, 2019)
Necrotizing pneumonia, rare complication of Community-acquired bacterial pneumonia (CABP), bear its own morbidity and mortality. Even though CABP generally respond well to the antibiotic treatment, but complications like empyema, necrotizing pneumonia with pneumatocoel formation (cavitary necrosis) supervene in mainly immune-compromised patient. Although cavitary necrosis is manifested as a severe disease, most children show complete recovery even without surgical treatment and have normal chest radiographs at long term. Some cases may required surgical intervention like tube thoracotomy or open thoracotomy. A case is presented of an infant that developed necrotizing pneumonia with pneumatocoel formation during treatment of bacterial pneumonia. Tube thoracotomy was performed due to conservative treatment failure.